2020
DOI: 10.12968/jowc.2020.29.sup9b.s1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for person-centred care in chronic wound care: A systematic review and recommendations for practice

Abstract: Background Chronic wounds affect an estimated 2.21 per 1000 population. They are a significant source of morbidity and affect individuals physically, psychologically, socially and financially. Person-centered care is one approach to improve patient outcomes in wound care as it values patients' perspectives, beliefs and autonomy and considers the person as a whole within the cultural context in which care is provided. Aim We aimed to review the evidence on the use of person-centered care (PCC) in chronic wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 66 publications
(120 reference statements)
0
38
0
1
Order By: Relevance
“…Provision of information booklet, workshops, and lectures were the modes of delivery of intervention used in these studies. [ 17 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provision of information booklet, workshops, and lectures were the modes of delivery of intervention used in these studies. [ 17 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[17–20] Mostly, these studies reported among patients with spinal cord injury or degenerative neurological diseases. [ 21 22 ] The evidence on the effect of educational interventions in reducing PU incidence is also low. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…In wound care, autonomy can, for example, mean that the patient can choose what kind of dressings they prefer to use. Holistic wound care and patients' autonomy have also been highlighted in the literature -especially in the context of person-centred care, which aims to improve not only clinical outcomes, such as wound healing, but also the patient's quality of life and level of satisfaction ( Gethin, Probst, Stryja, Christiansen & Price, 2020 ). In practice, the focus is on the patient as a whole, not on the wound in isolation, and staff work with patients to tailor the care to their needs ( Lindsay et al, 2017 ).…”
Section: Article In Pressmentioning
confidence: 99%
“…Both general and VLUspecific HL may affect VLU outcomes through affecting patient's adoption of health behaviours. Improvements in general and specific HL may improve patient knowledge and understanding of the benefits of adhering to VLU self-management recommendations [25][26][27] and support patients to adopt healthy behaviours in line with the agreed plan. For example, when choosing compression hosiery, patients may rely on HL to critique the options based on their analysis of comfort 28 which may be opposed to achieving maximum therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The management plan should be developed in collaboration with patients in a standard consultation 1 26 because shared decision making is paramount for a faster healing outcome. 27 An informed patient can participate as an essential partner in the VLU management process. 28 The patient’s role is complementary to their healthcare professional’s role, as they monitor symptoms, adhere to compression and adopt health behaviours, following the advice of health professionals.…”
Section: Introductionmentioning
confidence: 99%